Asian case studies what can we learn from them [review of] - Schaffer, Bernard (Philippine Journal of Public Administration, 1976)
A review of Gabriel U. Iglesias (ed.), Implementation, the Problem of Achieving Results: A Casebook on Asian Experiences (Manila, Philippines: EROPA, 1976), 403p.